Low expression of LncRNA AFAP1-AS1 inhibits proliferation and promotes apoptosis of non-small cell lung cancer cells through inhibiting wnt signaling pathway: LncRNA AFAP1-AS1 in non-small cell lung cancer cells - Sun, Ying; Fan, Liming; Li, Yixian (Cellular and Molecular Biology, 2023)
To detect the effects of long non-coding ribonucleic acid (lncRNA) actin filament-associated protein 1-antisense RNA1 (AFAP1-AS1) on the proliferation and apoptosis of non-small cell lung cancer (NSCLC) A549 cells and its mechanism. 1) The expression of lncRNA AFAP1-AS1 in NSCLC A549 cells was detected via quantitative reverse transcription-polymerase chain reaction (qRT-PCR). 2) The changes in proliferation and apoptosis of A549 cells after low expression of lncRNA AFAP1-AS1 were detected using cell counting kit-8 (CCK-8) and terminal deoxynucleotidyl transferase-mediated dUTP nick end labeling (TUNEL) assays. 3) The changes in Wnt signaling pathway proteins in A549 cells after low expression of lncRNA AFAP1-AS1 were detected using Western blotting. 1) The expression of lncRNA AFAP1-AS1 rose in A549 cells (P<0.01). 2) After low expression of lncRNA AFAP1-AS1, the growth of A549 cells was inhibited, and apoptosis was promoted. 3) After low expression of lncRNA AFAP1-AS1, the mRNA and protein expressions of glycogen synthase kinase (GSK) and β-catenin declined (P<0.05). Lowly-expressed AFAP1-AS1 inhibits the proliferation and promotes the apoptosis of NSCLC A549 cells via inhibiting the Wnt signaling pathway.